O (en)canto da linguagem rendada: ritmo e sonoridade em Tutameia, de Guimarães Rosa - Maíra Pinheiro Tavares (2024)
This work carried out an analysis of the last book published in his lifetime by João Guimarães Rosa, Tutameia: Terceiras estórias, following the journey already begun by many critical studies on the author's work. Our focus was on the care with which Rosa elaborates his text, like a lace structure, and tracing the elements that make the narratives enter the field of poetry. We work to discuss a book that critics have not yet studied from this perspective. Tutameia is made up of very short stories, in which the meanings are condensed into a few words. The main objective of this work was to investigate the use of resources traditionally attributed to poetry and their function in the prose of “Third Stories”. The most recurrent and most impactful are those that give the work musicality, such as rhythm and sound resources. Rosa seeks, with his musical language, to achieve an unprecedented vision, beyond common sense. The author of Tutameia calls on his reader to “open their heads to the totality”, that is, to observe the world from unconventional angles, clearing their eyes, to see (and hear) in a different way. In order to achieve this end, we believe that Rosa works so hard with language: to produce musical effects, which bring meanings to the senses. For Guimarães Rosa, as for Paul Valery, the words used in common language are insufficient to express “human truths”. Hence Rosa enters the sphere of sound experimentalism. To discuss this issue, in the first chapter, we made an overview of rosiana's critical fortune on the subject. In the second chapter, we discuss the complex and enigmatic architecture of the book, in which the paratexts distributed throughout Tutameia also build rhythm. In the third chapter, we read some stories, examining how musical language is engendered in narratives. And finally, in the fourth chapter, we explore how explicit references to music and constituent elements of the musical universe relate to the musicality of language in some narratives. Our basis for this analytical study references authors who studied rhythm and musicality in literature, such as Octavio Paz, Paul Valery, José Miguel Wisnik, Alfredo Bosi, Antonio Candido as well as scholars in the musical field such as maestro Sérgio Magnani, Bohumil Med and Murray Schaffer. In light of these studies, we hope to have demonstrated how Tutameia is a book where musicality plays an important role in the structure of the book and in the constitution of the stories.